Geometry and kinematics of the Grant Range brittle detachment system, eastern Nevada, U.S.A.: An end‐member style of upper crustal extension. Issue 9 (17th September 2015) - Long, Sean P.; Walker, Jerome P.
Abstract Documenting the range of styles of normal faulting is fundamental to understanding crustal extension. Here geologic mapping, field relationships, and deformed and restored cross sections illustrate the geometry and kinematic development of a system of west‐vergent detachment faults in the Grant Range in eastern Nevada. Faults exhibit brecciation and stratigraphic cutoff angles of 5–15° at all structural levels and deform a 10 km thick section of Paleozoic and Paleogene rocks. The fault system is folded across an anticlinal culmination, which grew during extension, as indicated by progressively increasing interlimb angles and incision in the axial zone. The eastern limb consists of an imbricate stack of faults that were emplaced from bottom to top. In the western limb, several faults exhibit apparent thrust relationships. The oldest faults are cut by a ~29 Ma dike, and the highest preserved fault cuts ~32 Ma volcanic rocks that restore to paleodepths of ~1 km. Retrodeformation of folding and minimal structural relief and angularity across a Paleogene unconformity indicate the faults were active at 5–15° angles. Retrodeformation of offset indicates ≥49 km (98%) extension. We propose a model of stationary, sustained isostatic uplift and incision at the culmination axis (a "fixed hinge"), with updip excision producing bottom‐to‐top growth of the imbricate stack and downdip excision producing apparent thrust relationships. The fault system exhibits similarities to core complex detachment systems, though it is confined to upper crustal levels, and there are no preserved high‐angle or listric normal faults, indicating a unique extension style dominated by low‐angle excision.